Ultra-stretchable yet tough, healable, and biodegradable triboelectric devices with microstructured and ionically crosslinked biogel. (September 2022) - Ghosh, Sujoy Kumar; Kim, Minsoo P.; Na, Sangyun; Lee, Youngsu; Park, Jonghwa; Cho, Seungse; Cho, Jeonghoon; Kim, Jae Joon; Ko, Hyunhyub
Abstract: To reduce the environmental impact of non-biodegradable electronic waste, developing sustainable technology with biomass-derived biodegradable materials are essential. However, the insufficient mechanical and electrical performances of the conventional biodegradable materials with planar structures often limit their use in bioelectronics. Here, we develop a high-performance ionic biogel device based on three-dimensional (3D) microstructured design of completely healable yet fully biodegradable biogel by using ionically cross-linked biomass resource, gelatin. The stress-absorbing geometry of 3D microstructure improves the mechanical resilience and facilitates highly elastic ( 4000%), notch-tolerable and extremely tough ( 10, 998 J/m 2 ) ionic biogels. In addition, the interlocked feature of 3D architecture provides the ionic diode characteristics of the biogel that enhances the triboelectric energy harvesting capability from external stimuli of pressure and temperature, even under an extreme stretching condition. Our triboelectric nanogenerator based on 3D ionic biogels exhibits excellent power output ( 325 mW/m 2 ), superior energy conversion efficiency ( 70.7%) and high-resolution mechano- ( 9 Pa) as well as thermo- ( 0.03 K) transduction functionalities with long-term stability. The 3D ionic biogel recovers its original electrical properties even after mechanical damage through self-healing. For proof-of-concept demonstrations, the gelatin biogel serve in soft and conformable electronic skins to monitor low-frequency vital signs and high-frequency acoustic waves, for haptic perception of surface textures, and in robotic tactile skins, providing a new benchmark as a clean and green technology for soft bio-electronic devices with zero waste. Graphical Abstract: ga1 Highlights: Ultra-stretchable yet tough, healable, and biodegradable triboelectric device is developed. Stress-absorbing microstructure improves the mechanical resilience and facilitates highly elastic and notch-tolerable ionic biogels. Ionic diode property of the biogel enhances the triboelectric performances from external stimuli of pressure and temperature.